KOMPETENSI ANALISIS KESALAHAN BERBAHASA SEBAGAI SOLUSI PEMBELAJARAN ASPEK KEBAHASAAN - Syamsul Ghufron (EDU-KATA, 2019)
This study aims to describe the principles of language learning, linguistic aspects of the Curriculum 2006 and Curriculum 2013, and the competence of error analysis as solutions of aspects gramatical learning. Data sources of qualitative research and literature are the books of language learning as well as Curriculum 2006 and Curriculum 2013. Data were collected with refering methods and the note techniques. Analyzing data qualitatively and interpreted by means of examining all the data, data reduction, making the abstraction and classification. The study concluded that the principle of language learning: aspects of gramatical are taught only to correct errors of students' language. Aspects of gramatical in the 2006 Curriculum includes the diction, sentences directly and indirectly, effective sentences and proper grammar, correct, and polite. Aspects of gramatical in the curriculum in 2013 is related to the activities of error analysis: identifying deficiencies text, examine and revise the text, evaluate the text, and edit text.